THE ROLE OF MADRASAH IN IMPROVING CHARACTER EDUCATION IN THE DIGITAL AGE - Siti Muhibah; Abdul Haq AS; Mohamad Sudi (Adisam Publisher, 2024)
The aim of the research is to obtain precise, complete and complex information about the role of madrasas in improving character education in the digital era. The method used is the library research method, the research sources used are secondary sources originating from research journals and relevant books related to the study sources. The research results show that, the role of madrasahs, madrasah heads and teachers is increasingly complex and urgent in the digital era, where the information era comes faster than the wind blowing towards students without limits and without boundaries. Apart from that, madrasas as educational institutions have a religious background, but they also do not ignore the technological tools needed for the elements in them to facilitate a quality learning process. School principals as managers must design and implement programs that are able to continue to encourage teachers and students to become brilliant individuals in accordance with current developments, accompanied by the development of morals, character and religious values. Teachers must also continue to develop themselves to improve their qualifications, competencies and skills in mastering technology to keep pace with student development. Then students must receive guidance on discipline, morals, good and religious values that is strict but friendly, continuous and trained, and happy. Maximum guidance, full attention. Interesting learning that is balanced with current developments.